2007
DOI: 10.1002/prot.21469
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural characterization of the catalytic domain of the starch synthase III from Arabidopsis thaliana

Abstract: Glycogen and starch are the major energy storage compounds in most living organisms. The metabolic pathways leading to their synthesis involve the action of several enzymes, among which glycogen synthase (GS) or starch synthase (SS) catalyze the elongation of the alpha-1,4-glucan backbone. At least five SS isoforms were described in Arabidopsis thaliana; it has been reported that the isoform III (SSIII) has a regulatory function on the synthesis of transient plant starch. The catalytic C-terminal domain of A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 49 publications
6
47
0
Order By: Relevance
“…Although the parameters for S. coelicolor GSase differ from those obtained for the E. coli homolog (44), they are very close to the parameters obtained in the characterization of the starch synthase III from Arabidopsis thaliana (14). It is well established that starch synthesis in plants and bacterial glycogen synthesis share similar properties in relation to their mechanisms and regulation steps (3,4).…”
Section: Resultssupporting
confidence: 68%
“…Although the parameters for S. coelicolor GSase differ from those obtained for the E. coli homolog (44), they are very close to the parameters obtained in the characterization of the starch synthase III from Arabidopsis thaliana (14). It is well established that starch synthesis in plants and bacterial glycogen synthesis share similar properties in relation to their mechanisms and regulation steps (3,4).…”
Section: Resultssupporting
confidence: 68%
“…At least five classes of SS are found in the developing endosperm, each with distinct catalytic properties with respect to substrate preferences and α-glucan product that is formed [176]. The SSs share structural characteristics with each other, and other glycosyltransferases, e.g., glycogen synthases, including a highly conserved K-X-G-G-L motif in the C-terminal domain that is responsible for substrate binding [176][177][178][179]. Variation amongst the SS isoforms is found in the N-terminus upstream of the catalytic core, and varies in length from 2.2 kDa in granule-bound starch synthase I to approximately 135 kDa in maize SSIII [180].…”
Section: Elongation Of α-Chains By Starch Synthasesmentioning
confidence: 99%
“…1B). It is important to mention that the comparison between the model and GS crystal structure revealed that the global topology is almost the same, except for differences in some loops [10,48]. Thus, the catalytic domain of AtSSIII, as well as the bacterial GSs share the same GT-B fold and were classified in the GT-5 family of glycosyltransferases.…”
Section: Role Of Sbds In Starch Synthase IIImentioning
confidence: 95%
“…AtSSIII, with a total of 1025 amino acid residues, is a particular enzyme since it contains a putative N-terminal transit peptide followed by a 557-amino acid SSIII specific domain (SSIII-SD) and a C-terminal catalytic domain of 450 amino acids [34,48]. We previously built a 3D structural model of the catalytic domain of AtSSIII using the structure of the glycogen synthase (GS, PDB ID 1RZU) from A. tumefaciens [48] (see also Fig.…”
Section: Role Of Sbds In Starch Synthase IIImentioning
confidence: 99%
See 1 more Smart Citation